2023
DOI: 10.1073/pnas.2219334120
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and vitamin D, two sides of the same coin, better to land on its edge to improve multiple sclerosis

Abstract: Previous studies revealed a latitudinal gradient of multiple sclerosis (MS) prevalence, increasing by moving from the equator to the poles. The duration and quality of an individual’s exposure to sunlight vary with latitude. Skin exposure to sunlight activates vitamin D synthesis, while light absence, as perceived by the eyes, activates melatonin synthesis in the pineal gland. Vitamin D or melatonin deficiency/insufficiency or overdose can occur at any latitude due to specific lifestyles and diets. Moving away… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Previous observational studies have noted that during sunnier summer months, melatonin levels are lower and last for shorter periods compared to winter ( 66 , 67 ). From the poles to the equator, with increasing sunlight intensity and duration, melatonin secretion decreases ( 68 , 69 ). This phenomenon is biochemically explained by excessive sunlight suppressing the activity of key enzymes in the synthesis pathway ( 70 , 71 ), while also activating melanopsin produced by retinal ganglion cells, thereby suppressing the synthesis and release of melatonin in the pineal gland ( 70 , 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies have noted that during sunnier summer months, melatonin levels are lower and last for shorter periods compared to winter ( 66 , 67 ). From the poles to the equator, with increasing sunlight intensity and duration, melatonin secretion decreases ( 68 , 69 ). This phenomenon is biochemically explained by excessive sunlight suppressing the activity of key enzymes in the synthesis pathway ( 70 , 71 ), while also activating melanopsin produced by retinal ganglion cells, thereby suppressing the synthesis and release of melatonin in the pineal gland ( 70 , 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation of our study results lies in the fact that the pineal gland is connected through neural paths with the eyes and melatonin produce is suppressed by the light stimulus ( Sandyk, 1997 ). The incidence of MS is higher in geographical places with shorter daylight ( Ghareghani et al, 2023 ). This can in part potentially be explained by the suppression of melatonin produced by the excessive (artificial) light stimuli during the night.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, current studies showed a beneficial effect of melatonin as a supplement in relieving some of the MS symptoms and improving the quality of life ( Skarlis and Anagnostouli, 2020 ). Moreover, the research is being conducted on melatonin as a therapeutic option in the design of therapy regimens in MS ( Ghareghani et al, 2023 ). Pineal volume can reflect the production of melatonin, given that ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of the "latitude gradient" posits that there is a positive correlation between distance from the equator and multiple sclerosis risk (18). This notion has stimulated inquiries into plausible environmental stimuli, such as vitamin D insufficiency resulting from diminished sunlight exposure in regions situated at higher latitudes (22,23).…”
Section: Risk Factors Of Msmentioning
confidence: 99%